The California Indians; a source book. - Heizer, Robert F. (Robert Fleming), 1915-1979; Whipple, Mary Anne (University of California Press, 1971)
A comprehensive survey of California Indian native cultures, discussing their origins, traditions, beliefs, daily life, struggles, and culture.